The Revival of the Usage of Natural Fibers and Natural Dyes in Indonesian Textile - Dian Widiawati (Journal of Visual Art and Design, 2009)
Indonesia is known to possess abundant natural resources as well as a diverse textile tradition. Some examples of traditional textile materials are those made from indigenous natural fibers, such as silk, cotton, ramie, pineapple fibers, and banana frond fibers, which make use of natural dyes. The specific natural back ground and unique cultural tradition of a region strongly influence the creative process of local textile artisans and the visual form of textile works. After the invention of synthetic dyes, the usage of natural dyes has gradually decreased. However, the optimism in using traditional dyes recently emerges in the textile world in Indonesia. This tendency grows along with the issues of awareness of nature and the soaring popularity of back-to-nature lifestyle. This study attempts to identify the relations between the usage of natural dyes in the past and its relevance to contemporary contexts. This study focuses on several topics, firstly the past role of natural dyes and the invention of synthetic dyes which outgrow natural dyes. Then, this study aims to explain why natural dyes are recently being reused in textile, which leads to identifying the contemporary position or role of natural dyes, besides the existence of synthetic dyes which technically possess various advantages. This study also aspires to identify the advantages and shortcomings of natural dyes based on the consumers' acceptance and certain contexts. The method used in this study is the qualitative descriptive method through interdisciplinary approaches.